Corporate ownership, governance and tax avoidance: an interactive effects - Annuar, Hairul Azlan; Salihu, Ibrahim Aramide; Sheikh Obid, Siti Normala (Elsevier, 2014)
Although tax avoidance practices are as old as taxes themselves, the ways they are being perpetrated among corporate taxpayers have transmuted so sophisticated in recent times. This study thus proposes models for empirical investigations into the relationship between corporate ownership structure and corporate tax avoidance in Malaysia. It was argued, based on cost/benefits consideration of tax avoidance, that family; foreign and government ownerships could be associated with corporate tax avoidance among Malaysian listed companies. The study further proposes that strong governance mechanism could mitigate such association. Two econometrics dynamic panel data models are proposed for the investigation. Generalized Method Moment (GMM) estimator is recommended as the estimation method.